(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
In the rapidly evolving digital era, social media has become integral to daily life, especially among students. It offers various benefits, including ease of communication, access to learning resources, and opportunities for self-development. This community service program aims to raise awareness about digital ethics and security among students, particularly at MI At-Taqwa . Given the rapid growth of information technology and the widespread use of social media among young people, it is essential to educate students about digital ethics, personal data protection, and the negative impacts of issues such as cyberbullying and misinformation. The program will consist of workshops and seminars divided into several sessions, where students will receive training and simulations. These will focus on improving their understanding of ethical behavior in online interactions and how to safeguard their personal information. Evaluation results indicate that 85% of students demonstrated increased knowledge of digital ethics, 80% became more cautious about sharing personal data, and 75% developed a more critical approach to handling fake news. Overall, this program has proven effective in raising digital awareness and positively influencing students’ safe and responsible use of social media.